LEAP From Pilot to Scale: Embedding Digital Reading within the Kenya National Library Service - Heavner, Rachel; Lowe, Zev; Mwachi-Amolo, Joan (2017)
Mobile technologies have become more normalized for data collection, education for displaced communities and interventions at a distance. Yet, questions remain around how to effectively bring these technology interventions from pilot efforts to broad scale adoption. Worldreader is demonstrating operational success in its digital reading programs in Kenya. In 2014, Worldreader, in partnership with the Kenyan National Library Service (knls), launched its digital reading program, called LEAP (Libraries E-reading Activities Partnership) in eight libraries. By December 2017, LEAP had successfully scaled to all 61 public libraries in the country. This paper outlines five key insights for moving from pilot to country-level scale: 1. Start slow, start smart 2. Leverage economies of scale 3. Step by step: Implement in phases 4. Manage change: Creating a unified vision of success 5. Implement sustainability from the start. These learnings can inform others leveraging technology to improve education around the world and contribute to strengthening an effective, responsible and efficient ecosystem of technology-enriched educational programs.
KerkoCite.ItemAlsoKnownAs: 2339240:IGJL4PW2 2405685:GNGTW6N4
Keywords: ⛔ No DOI found

An Atlas of The Forty Colleges of Education in Ghana - Haßler, Björn; Akunor, J. T.; Nyamador, E. S. (2017)
EdTechHub.Source: 2129771:F7ZRYUZX shortDOI: 10/ghgk6m KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3911076 10/ghgk6m 2129771:F7ZRYUZX 2129771:U3IVX9WX 2405685:SKFNBK29
Keywords: _DOILIVE; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode